Demographic variables and clinical profile of scrub typhus patients: experience from a tertiary care center in Udaipur, Rajasthan - Choudhary, Suresh; Dixit, Mukul; Verma, Anjana; Mittal, Hemlata; Mathur, Medha (International Journal Of Community Medicine And Public Health, 2021)
Background: Scrub typhus is an acute febrile bacterial zoonoses, caused by Orientia tsutsugamushi and is associated with a range of complications, including sepsis, Acute respiratory distress syndrome (ARDS), pre-renal azotemia and Multiorgan dysfunction syndrome (MODS). The objective of this study was to study the demographic variables and clinical profile of the patients diagnosed with scrub typhus. admitted in a tertiary care hospital in Udaipur, Rajasthan. Methods: It was a longitudinal, observational study, conducted in a tertiary care centre in Udaipur, Rajasthan from January 2020-June 2021. All patients, diagnosed (positive for antibody IgM) with scrub typhus in the hospital during the study period were included in the study. Information about the patients was collected using a pre-tested questionnaire and clinical examination, after taking the informed consent from the study participants. Results: Mean age of the patients was 36.4±19 years. Majority (69.4%) of the patients were from rural area and fever was the most common (83.9%) symptom experienced. Eschar was found in only 1.6% of patients. About 87.1% of the patients had complications, with MODS, being the most common affecting about 34% of the total patients. The patients from rural areas were found to have significantly higher odds (OR=1.61) of having complications as compared to urban area patients (CI=1.09-4.3). Conclusions: This article draws attention to the fact that scrub typhus is quite on rise and most of the cases are associated with complications. There is a need to develop effective strategies and interventions to stop this rampant rise of the cases in India.